2014
DOI: 10.1083/jcb.201305070
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 kinase switches cell fate from apoptosis to necrosis following TNF stimulation

Abstract: Activation of the TAK1 kinase drives RIPK3-dependent necrosis and inhibits apoptosis downstream of TNF-α stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 60 publications
3
109
1
Order By: Relevance
“…The other is that additional deletion of Tak1 in Tab2-deficient fibroblasts solely induces caspasedependent apoptosis following TNFa stimulation. 49 These results collectively reveal an unexpected role of TAK1 in cell death pathways, as an inducer of necroptosis ( Figure 3). Furthermore, it has been shown that TAK1 activates RIPK3, reciprocally RIPK3 activates TAK1, and these activations are facilitated by RIPK1, which mediates TAK1-RIPK1-RIPK3 binding.…”
Section: Tak1 As a Necroptosis Inducermentioning
confidence: 72%
See 4 more Smart Citations
“…The other is that additional deletion of Tak1 in Tab2-deficient fibroblasts solely induces caspasedependent apoptosis following TNFa stimulation. 49 These results collectively reveal an unexpected role of TAK1 in cell death pathways, as an inducer of necroptosis ( Figure 3). Furthermore, it has been shown that TAK1 activates RIPK3, reciprocally RIPK3 activates TAK1, and these activations are facilitated by RIPK1, which mediates TAK1-RIPK1-RIPK3 binding.…”
Section: Tak1 As a Necroptosis Inducermentioning
confidence: 72%
“…[46][47][48] Inhibition of TAK1 is usually followed by caspase-8 and -3 activation in response to TNFa, which suggests that TAK1 inhibits caspase activation cascade to block apoptotic cell death. 49 Thus, TAK1 is likely to blunt the formation or activation of Complex IIa. Recent studies revealed two major mechanisms through which TAK1 inhibits caspase activation ( Figure 2).…”
Section: Tak1 Inhibits Apoptosismentioning
confidence: 99%
See 3 more Smart Citations